Implementasi Metode Analytical Hierarchy Process (AHP) - Weighted Product (WP) dalam Sistem Pendukung Keputusan untuk Rekomendasi Pelanggan Terbaik berbasis Website (Studi Kasus: PT. Pelabuhan Indonesia IV (Persero) Makassar) - Niftah Fatiha Armin; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
At PT. Pelabuhan Indonesia IV, of course, there are customers who cooperate and become company partners. Customers who have contributed positively to the growth and progress of the company will have the opportunity to get an award as the best customer. A customer can be said to contribute positively by remaining a partner of the company. With this award, customers can be more enthusiastic to continue using the services of PT. Indonesian Port IV. Including in the economic sector, without customers, economic growth in remote areas will be less developed because one of the biggest modes of transportation is using ships or containers. In determining the best customer PT. Port of Indonesia IV is still using a manual process. This is an obstacle for PT Pelabuhan Indonesia IV Makassar. Therefore, to get the best client advice at PT. Pelabuhan Indonesia IV Makassar, thea researcher's decision on thea grounds that the AHP-WP technique is the right technique to be run into a system that supports it in accordancea with the consideration of the consistency of the evalauation results that have been carried out by looking at the existing variables. Solving the problem in this research is by implementing the Analytical Hierarchy Process (AHP) - Weighted product (WP) technique to get the best client advice at PT. Port of Indonesia IV Makassar. Based on the application of the AHP - WP methoad obtained from the system, it can be declared valid. The accuracy results of 80% obtained from accuracy testing with the results of the questionnaire as many as 8 respondents who have accurate results on thle Analytical Hierarchy Process methodi.